Edukasi Tabungan Simpanan Pelajar (SIMPEL) bagi Siswa SMP Islam Al Azhar 25 Tangerang Selatan - Irawati, Wiwit; Akhsani, Novi; Nurbaeti, Nurbaeti (ABDIMAS Iqtishadia, 2023)
This Community Service is motivated by the lack of financial literacy in Al Azhar 25 Islamic Middle School which is still low. As one of the schools that has a number of students from various middle to upper socio-economic backgrounds, Al Azhar Middle School students have the competency to set aside some of their pocket money and save. Simpel is one of OJK's initiatives to expand access to finance for students as well as teach and familiarize them with managing money from an early age. This PKM is implemented with the aim of raising awareness and habits of saving so that it can help students manage their finances independently in the future. The method for implementing PKM uses the counseling method regarding Education about Student Savings Savings (SIMPEL) and the question and answer method afterwards. The result of this Community Service is the growing awareness of the importance of saving and the growing habit of managing finances wisely by Al Azhar 25 Islamic Middle School students.